Metabolic crisis index as a predictor for metabolic crisis in endurance horses - Adamu, Lawan (2014)
In Malaysia, equine endurance race is an event conducted on natural tracks over distances ranging from 40 to 120 km over a period of 24 hours. This event, under challenging physical conditions involves both aerobic and anaerobic metabolisms of the horse. The intense physical activity over an extended period often causes susceptible horses to develop metabolic crises resulting in elimination from races. Metabolic crisis is the extreme changes associated with the combination of the physical parameters that result in the complex and detrimental physiological and biochemical alterations leading to elimination of endurance horses from the race. Metabolic abnormalities in horses under extreme conditions are re°ected by abnor- malities in physical and blood parameters during and after physical activity. The development of metabolic crises in horses during endurance races is unpredictable. This is due to the fact that there is no established method to determine, before the race that a horse is not ¯t to participate in an endurance race. It was pos- tulated that the physical and blood parameters of horses that develop metabolic crisis and eliminated during endurance races di®ered signi¯cantly from those of horses completing the race successfully. Thus the objectives of this study were to determine the risk factors for horses to develop metabolic crises during endurance races and to develop a method to predict before the race, that a horse may poten- tially develop the crises. The subjects for the study were horses participating in 19 endurance races held between March 2010 and December 2012 in several states of Malaysia. Three hundred and seventy ¯ve Arabian (n = 152) and Arabian cross (n = 223) endurance horses aged from 6 to 15 years and weighing between 350 and 450 kg involved in these races were selected for the study. The height of these horses ranged from 14 hands 2 inches and 16 hands 1 inch. There was no sex preference for horse selection and only apparently healthy horses were included in the study. Of these horses 253 developed metabolic crises and 122 completed the race successfully. Among the 253 eliminated endurance horses, 122 were se- lected randomly from establishments A, B, and C to represent this category. Sixty one horses in each independent category was represented by pre and post-ride completed, pre and post-ride metabolic. All horses were physically examined and physical data such as skin recoil, mucous membrane colour, capillary re¯ll time and intestinal motility were obtained before the race and after 20 to 30 minutes of recovery period. Blood samples were collected at pre- and post-race periods to determine haematological, plasma electrolyte and plasma biochemical parameters including glutathione reductase (GR), serum amyloid-A (SAA) and interleukin-6 (IL-6). The mean environmental humidity and ambient temperature during the endurance races were 71.73 § 4.05 % and 29.06 § 1.1oC respectively. The study showed that Arabian cross horses were more prone to develop metabolic crises than pure Arabian horses. Among the parameters analysed in this study, the signi¯cant (p<0.05) ¯ndings in horses with metabolic crisis were increased packed cell volume (0.66 § 0.19 LL¡1), creatine kinase (1988 § 1447 UL¡1) and IL-6 (3.25 § 3.95 ng/ml), decreased GR (10.91 § 3.95 ng/ml) and chloride (89.6 § 4.4 mmol/L). These changes are characteristic of metabolic crises in horses are associated with muscle damage due to physical activity, increased sweating without water replen- ishment, and the inherent inability of horses to neutralise the increased reactive oxygen species production during endurance races. Using the plasma biochemical parameters which are strongly associated with metabolic crises with a correlation coe±cient of (r = 0.8790; P < 0.001), a new method called Metabolic Crisis Index (MCI) was developed as a predictor for horses with potential to develop metabolic crisis in endurance races. This index, tested in an endurance competition and by using retrospective data from previous and on going competitions indicated a higher value greater than 5.5 for those eliminated and lower value below 5.5 for those that completed the race successfully, this proved to be accurate in the prediction of metabolic crisis in endurance horses. The MCI is an innovative and simple method use as a prediction method that will assist the equine endurance society to reduce the rate of elimination and to safeguard against serious medical problems during endurance races in the tropics.